Pengaruh Tingkat Pengetahuan Dan Kualitas Pelayanan Aparatur Sipil Negara Terhadap Efektivitas Program Smart Governance I-ceta Di Kabupaten Indramayu - Brillianto, Gagas; Astuti, Yuhana (eProceedings of Management, 2024)
Indramayu Regency is one of the districts designated by Kominfo as a city or district program "towards 100 smartcities". As the implementer of the smart city program, Indramayu Regency needs to evaluate the State Civil Apparatus(ASN) of West Indramayu Regency as the implementer of the smart city program. By knowing the level of Knowledgeand quality of service from ASN West Indramayu Regency can provide benefits that are in accordance with thesolutions or needs expected by the community. The purpose of this study was to determine the effect of the level ofknowledge and quality of ASN services on the effectiveness of the I-CETA (Indramayu Cepat Tanggap) smartgovernance program. This study uses quantitative methods with a population of 178 State Civil Apparatus (ASN) ofWest Indramayu district. The theory used in this study is to use the smart governance theory put forward by Subkhan.The analysis technique used in this research is multiple linear regression analysis techniques with samplingtechniques using saturated samples in Indramayu district. Based on the results of multiple linear regression analysis,the results show that the level of knowledge and service quality produce a significant and positive effect partially orsimultaneously from the variable level of knowledge and service quality on the effectiveness variable. The results ofthe research presentation can serve as a basis for the development of subsequent researchers and suggestions for the Indramayu district government to increase the effectiveness of the smart governance program in terms of employee knowledge levels and service quality. Keywords-knowledge level, service quality, effectiveness, smart city, smart governance